Lancemaside A, a major triterpene saponin of Codonopsis lanceolata enhances regulation of nitric oxide synthesis via eNOS activation - Young Seok Lee; HeeEun Kim; Jinhye Kim; Geun Hee Seol; Kwang-Won Lee (BMC, 2019)
Abstract Background Many studies on the effect of saponin-rich Codonopsis lanceolata as a bioactive source for improving physical health have been performed. C. lanceolata contains triterpenoid saponins, including lancemasides. These saponins are known to be particularly involved in the regulation of blood pressure or hypertension. This study investigated whether lancemaside A (LA), a major triterpenoid saponin from C. lanceolata, regulates nitric oxide (NO) production via the activation of endothelial NO synthase (eNOS) in human umbilical vein endothelial cells. Methods Upon separation with petroleum ether, ethyl acetate, and n-butanol, LA was found to be abundant in the n-butanol-soluble portion. For further purification of LA, HPLC was performed to collect fraction, and LA was identified using analysis of LC/MSMS and 13C-NMR values. In in vitro, the effects of LA on NO release mechanism in HUVECs were investigated by Griess assay, quantitative real-time reverse-transcription PCR, and Western blotting. Results Our results showed that NO production was efficiently improved by treatment with LA in a dose-dependent manner. In addition, the LA treatment resulted in extensive recovery of the NO production suppressed by the eNOS inhibitor, L-NAME, compared with that in the control group. Additionally, the level of eNOS mRNA was increased by this treatment in a dose-dependent manner. These results suggested that LA is an inducer of NO synthesis via eNOS mRNA expression. Also, the study indicated that LA is involved in activating the PI3K/Akt/eNOS signaling pathway. Conclusion These results suggested that LA is an inducer of NO synthesis via eNOS mRNA expression. Also, the study indicated that LA is involved in activating the PI3K/Akt/eNOS signaling pathway. These findings suggest the value of using LA as a component of functional foods and natural pharmaceuticals.